Acquired von Willebrand disease associated with smoldering multiple myeloma and hereditary hemorrhagic telangiectasia successfully treated with daratumumab, pomalidomide, and dexamethasone: hitting three birds with one stone? – case report - Amaeshi, Lemchukwu; Poston, Jacqueline N.; Gergi, Mansour (Frontiers in Hematology, 2025)
Acquired von Willebrand disease (AvWD) is a rare bleeding disorder that results from a structural or functional defect of von Willebrand factor. AvWD is often associated with a variety of underlying diseases, most frequently lymphoproliferative, myeloproliferative, and cardiovascular disorders. In this report, we present a unique case of a patient presenting with AvWD secondary to smoldering myeloma (SMM) but also found to have hereditary telangiectasias (HHT). While AvWD is not part of the defining criteria for a diagnosis of myeloma in patients with SMM, aggressive anti-myeloma treatment in this case led to a complete resolution of the bleeding disorder. Interestingly, since pomalidomide is an effective agent in HHT, a pomalidomide-based treatment was able to manage all 3 of the patient’s hematologic disorders. This case adds to the body of literature supporting the efficacy of aggressive antimyeloma therapy as a definitive treatment in monoclonal gammopathy-associated AvWD and presents an alternative option to traditional supportive therapy, especially in patients with persistent bleeding.